Effectiveness of board of directors’ composition on performance of government parastatals: A case of parastatal institutions in Tanzania - Msigwa, Elvis (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the Requirements of the award of Master’s Degree of Business Administration Corporate Management (MBA-CM) of Mzumbe University